2022
DOI: 10.1002/jcla.24216
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for predicting severity and mortality in hospitalized COVID‐19 patients

Abstract: Background: Coronavirus disease 2019, COVID-19, has reached all the corners of the world and was declared by the WHO as a global pandemic and public health emergency of international concern on the January 31, 2020. Allocating quick and specific biomarkers to predict the disease severity upon admission to hospital became a crucial need. This study, therefore, aimed at exploring the relationship between laboratory results in COVID-19 patients admitted to hospital and the final outcome in these patients. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…Though our study observed a higher ferritin level in non‐survivor patients, it did not prove it as a significant risk factor of ICU admission or mortality when adjusted for other factors. This observation has similarity with other studies (Aljohani et al, 2022; Carubbi et al, 2021) but contrast with other study where higher ferritin is said to be a risk factors of severe disease and mortality (Ahmed et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Though our study observed a higher ferritin level in non‐survivor patients, it did not prove it as a significant risk factor of ICU admission or mortality when adjusted for other factors. This observation has similarity with other studies (Aljohani et al, 2022; Carubbi et al, 2021) but contrast with other study where higher ferritin is said to be a risk factors of severe disease and mortality (Ahmed et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we evaluated plasma CK-BB levels to detect neurological damage that may develop with the severity of COVID-19 pneumonia. In previous studies, parameters such as ferritin, CRP, pro-BNP, troponin-I, fibrinogen, d-dimer, neutrophil-lymphocyte ratio, procalcitonin, and IL-6 were found to be prognostic biomarkers in COVID-19 pneumonia (30)(31)(32). In our study, these biomarkers were found to be high in intensive care patients with severe pneumonia symptoms (p<0.01), while serum CK-BB levels did not change (p>0.05).…”
Section: Discussionsupporting
confidence: 55%
“…The COVID-19 pandemic remains a public health emergency of global significance that threatens human health and welfare [ 19 ]. Therefore, in this retrospective cohort study, clinical and laboratory data from 300 confirmed cases of COVID-19 admitted to the Hospital Nacional Almanzor Aguinaga Asenjo (HNAAA) in Peru were analyzed.…”
Section: Discussionmentioning
confidence: 99%